An Emerging Role for Neutrophil Extracellular Traps in IgA Vasculitis: A Mini-Review - Chen, Xiu-Qi; Tu, Li; Tang, Qing; Huang, Li; Qin, Yuan-Han (Frontiers in Immunology, 2022)
Immunoglobulin A vasculitis (IgAV) is the most common systemic small vessel vasculitis in childhood. Its clinical manifestations are non-thrombocytopenic purpura, accompanied by gastrointestinal tract, joint, kidney and other organ system involvement. The pathogenesis of IgAV has not been fully elucidated. It may be related to many factors including genetics, infection, environmental factors, and drugs. The most commonly accepted view is that galactose-deficient IgA1 and the deposition of IgA and complement C3 in small blood vessel walls are key contributors to the IgAV pathogenesis. Extensive neutrophil extracellular traps (NETs) in the peripheral circulation and skin, kidney, and gastrointestinal tissue of patients with IgAV has been identified in the past two years and is associated with disease activity. This mini-review provides a possible mechanism for NETs involvement in the pathogenesis of IgAV.